2019
DOI: 10.5334/aogh.2340
|View full text |Cite
|
Sign up to set email alerts
|

SOSAS Study in Rural India: Using Accredited Social Health Activists as Enumerators

Abstract: Background: Global estimates show five billion people lack access to safe, quality, and timely surgical care. The wealthiest third of the world’s population receives approximately 73.6% of the world’s total surgical procedures while the poorest third receives only 3.5%. This pilot study aimed to assess the local burden of surgical disease in a rural region of India through the Surgeons OverSeas Assessment of Surgical Need (SOSAS) survey and the feasibility of using Accredited Social Health Activis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…According to the World Bank 2019 data, within South Asia, India was reported to have a lower number of physicians per 1000 individuals compared to Pakistan (0.7 vs. 1.1) (28). However, in correlation to the SOSAS study conducted in 2019 by Cherukupalli et al (5), the unmet surgical need in rural India was reported to be 6.5%, which is much lower than a staggering 14.3% in Pakistan as identified in this study.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…According to the World Bank 2019 data, within South Asia, India was reported to have a lower number of physicians per 1000 individuals compared to Pakistan (0.7 vs. 1.1) (28). However, in correlation to the SOSAS study conducted in 2019 by Cherukupalli et al (5), the unmet surgical need in rural India was reported to be 6.5%, which is much lower than a staggering 14.3% in Pakistan as identified in this study.…”
Section: Discussioncontrasting
confidence: 43%
“…Considering that greater than 50% of the population in the least developed regions worldwide is children, we can surmise that the surgical burden amongst children in LMICs is immense (3, 4). Currently, a large disproportion exists between the wealthiest and poorest third of the population globally, with the wealthy receiving a major share of 73.6% of surgical procedures and the poor receiving only 3.5% (5). Within poor countries, surgical services are concentrated almost wholly in cities and reserved largely for those who can pay for them (1).…”
Section: Introductionmentioning
confidence: 99%
“…Investigating the reasons underlying these differences would require assessment of data coverage and completeness for HMIS and further breakdown by surgical conditions to better match the inclusion of the surgical condition across studies. Our population-based met need calculations cannot be compared with small-scale household surveys investigating lifetime surgical uptake (50) or studies using self-report instruments such as SOSAS (18, 19).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the LCoGS and DCP3, small-to-medium scale regional studies have looked at surgical need in rural and urban areas (1719). The national-level surgical need benchmark using data from a universal healthcare coverage (UHC) cohort (n = 88,273, Contributory Health Service Scheme (CHSS) members) was estimated to be 3646 procedures per 100,000 people (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation